Successful Resuscitation and Use of VA ECMO Following Cardiovascular Collapse during Ethanol Sclerotherapy - A Case Report - Sella, Orie; Gal-Oz, Amir; Kori, Isaac; Carmi, Uri; Lichter, Yael; Nimrod, Adi; Fiszer, Elisheva (Archives of Clinical and Medical Case Reports, 2024)
Ethanol sclerotherapy is widely used for the treatment of vascular malformations and can rarely lead to fatal cardiopulmonary collapse due to pulmonary vasospasm and right heart failure, pulmonary embolism, or cardiac arrhythmias. We present a case of successful resuscitation after sudden cardiovascular collapse with the use of venous-arterial extracorporeal membrane oxygenation (ECMO) in an eighteen year old female following ethanol sclerotherapy for a venous malformation. This report raises awareness of the most fatal and rare risk factors for ethanol sclerotherapy. More research is needed to determine the efficacy of invasive monitoring techniques such as continuous pulmonary artery pressure monitoring in preventing such complications during sclerotherapy procedures.